Furnishing in style - Storey, Walter Rendell (New York : American Studio Books, 1947)
The first part of this book, the various historical styles in use today are illustrated by authentic originals. Only significant examples have been chosen, the endeavor being to convey the typical flavor of each influential style or period. In the latter part of this books, the illustrations show how today's architects, designers and decorators, using both traditional and contemporary designs, develop varied and colorful interiors which are at the same time consistent and suited to present day customs and needs.
Keywords: FURNITURE -- INTERIOR DECORATION